2004
DOI: 10.1093/toxsci/kfh142
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Male Reproductive System Effects After in Utero and Lactational 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) Exposure in Three Differentially TCDD-Sensitive Rat Lines

Abstract: Male reproductive effects induced by in utero and lactational exposure to TCDD were analyzed in three rat lines that are differently sensitive to TCDD. Rats from lines A, B, and C were selectively bred from TCDD-resistant Han/Wistar (Kuopio, H/W) and TCDD-sensitive Long-Evans (Turku/AB, L-E) rats and exhibited very different LD50 values for TCDD: >10,000, 830, and 40 microg/kg in males, respectively. The resistance in line A rats was linked to a mutated H/W-type aryl hydrocarbon receptor (Ahr(hw)) and in line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 37 publications
2
51
0
Order By: Relevance
“…Following exposure to TCDD in adult life, strains with a mutated AHR allele had a less pronounced decrease in spermatogenesis than those with the wild-type receptor [21]. Similarly, when exposed to the same compound in utero, males of the rat strains carrying the mutated allele had a lower decrease in daily sperm production and epididymal sperm reserves than counterparts with the wild-type allele when measured on postnatal day 70 [22]. Thus, the effects of TCDD exposure on spermatogenesis seemed to be decreased in rats with a mutated AHR, implying that a fully functioning receptor is needed for maximal negative exposure effects on spermatogenesis.…”
Section: Gene-environment Interaction and Animal Studiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Following exposure to TCDD in adult life, strains with a mutated AHR allele had a less pronounced decrease in spermatogenesis than those with the wild-type receptor [21]. Similarly, when exposed to the same compound in utero, males of the rat strains carrying the mutated allele had a lower decrease in daily sperm production and epididymal sperm reserves than counterparts with the wild-type allele when measured on postnatal day 70 [22]. Thus, the effects of TCDD exposure on spermatogenesis seemed to be decreased in rats with a mutated AHR, implying that a fully functioning receptor is needed for maximal negative exposure effects on spermatogenesis.…”
Section: Gene-environment Interaction and Animal Studiesmentioning
confidence: 94%
“…Thus, the effects of TCDD exposure on spermatogenesis seemed to be decreased in rats with a mutated AHR, implying that a fully functioning receptor is needed for maximal negative exposure effects on spermatogenesis. Although it is not fully explained how a mutated AHR can protect against the deleterious effects of dioxin on sperm number, the paper by Simanainen et al [22] showed that the effect is not mediated through reduction in testosterone production or poor development of seminal vesicles.…”
Section: Gene-environment Interaction and Animal Studiesmentioning
confidence: 99%
“…Among rats, differences between strains are seen due e.g. to aberrant AhR in TCDD-resistant strains (Simanainen et al 2004). Also salmonid strains differ greatly in their susceptibility to DLCs (Hornung et al 1996a), due e.g.…”
Section: Species Strain and Other Taxonomic Differences And Extrapolmentioning
confidence: 99%
“…2002;10 Hendriks &Enserink 1996, based on levels in 1950's-70's (extrapolated from CB 153 andΣPCBs) Powell & al. 1997a for double-crested cormorant; 12 13 Based on mean TEq values for the main diet species sprat in GF ) and BP 14 Storr- 15 ; WHO-TEqs for fish have been used; 16 Hario & al. 2004, conversion 19 Powell & al.…”
Section: Risk and Uncertainty Characterizationmentioning
confidence: 99%
“…Although WH rats have been extensively used in the risk assessment of various chemicals, a substrain of WH rats, named Han/Wistar (Kuopio), has toxicities caused by dioxins (Pohjanvirta et al, 1993). In addition, between Long-Evans (L-E) and Han/Wistar (Kuopio) rat strains, there is a difference in susceptibiland reproductive disorders, depending on the different aryl hydrocarbon receptor (AhR) sequence (Pohjanvirta and Tuomisto, 1994;Viluksela et al, 2000;Simanainen et al, 2002Simanainen et al, , 2004. However, it is not known whether there is a difference in the transactivation activity depending on the AhR sequence among rat strains.…”
mentioning
confidence: 99%